2020
DOI: 10.3389/fonc.2020.01452
|View full text |Cite
|
Sign up to set email alerts
|

Refocusing the Use of Psychiatric Drugs for Treatment of Gastrointestinal Cancers

Abstract: Gastrointestinal cancers (GICs) are the most common human tumors worldwide. Treatments have limited effects, and increasing global cancer burden makes it necessary to investigate alternative strategies such as drug repurposing. Interestingly, it has been found that psychiatric drugs (PDs) are promising as a new generation of cancer chemotherapies due to their anti-neoplastic properties. This review compiles the state of the art about how PDs have been redirected for cancer therapeutics in GICs. PDs, especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…The anticancer properties of antidepressant drugs in adjuvant cancer therapy have been previously reported [19,20]. Although, previous data support the beneficial role of antidepressant drugs in glioma, the molecular mechanisms involved in these drugs have not been established.…”
Section: Discussionmentioning
confidence: 98%
“…The anticancer properties of antidepressant drugs in adjuvant cancer therapy have been previously reported [19,20]. Although, previous data support the beneficial role of antidepressant drugs in glioma, the molecular mechanisms involved in these drugs have not been established.…”
Section: Discussionmentioning
confidence: 98%
“…These results are particularly interesting as it has recently been shown that psychiatric drugs offer potential as anti-cancer therapeutics ( Loehr et al, 2021 ). Moreover, a recent review has specifically addressed the need to investigate psychiatric drugs for treatment of gastrointestinal cancers ( Avendaño-Félix et al, 2020 ). We hypothesise that Crizotinib, Lapatinib, and Dasatinib are amongst the drugs with the most potential.…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancer (CRC), PMTZ not only suppresses the proliferation of cancer cells but also initiates mitochondrial apoptosis through the PI3K/AKT pathway (61). Additionally, research has illuminated PMTZ's capacity to induce autophagy in pancreatic ductal adenocarcinoma (PDAC), where it functions as an antagonist of proliferation (62). Furthermore, PMTZ has demonstrated a potent inhibitory impact on the proliferation of both human and murine…”
Section: Promethazine (Pmtz)mentioning
confidence: 99%
“…Initiating of autophagy-associated apoptosis through AMPK activation and PI3K/AKT/mTOR inhibition (60), promotes apoptosis by suppressing the PI3K/AKT signaling pathway (61), hinders proliferation and induces autophagy by increasing LC3II and p62 levels in cancer cell lines (62).…”
Section: Promethazinementioning
confidence: 99%
See 1 more Smart Citation